Improving student engagement and development through assessment : theory and practice in higher education - Clouder, Deanne Lynn (Routledge, 2012)
Against a backdrop of massification and the associated increase in student diversity there is an escalating requirement for personalized, technology driven learning in higher education. How does one engage and retain a group of students of such diverse culture, ethnicity, ambition and experience?